Positive T wave overshoot as a sign of ventricular enlargement. Issue 3 (March 1984) - Short, D; Weir, J
Abstract : A consecutive series of 86 patients with an inverted T wave showing terminal positivity (overshoot) of a specific pattern in the resting electrocardiogram were studied. Patients with bundle branch block or electrocardiographic evidence of acute infarction and those taking digoxin or a similar drug were excluded. In 67 patients the heart was examined by echocardiography and in a further two by direct inspection. Sixty six of the 69 patients had an abnormal thickness of the left (or right) ventricle or a calculated left ventricular mass greater than 200 g. Seven of the patients examined by echocardiography had clinically pure ischaemic heart disease; all showed evidence of left ventricular enlargement. In only 39 of the 63 patients with anatomical evidence of left ventricular hypertrophy or dilatation did the electrocardiogram satisfy the standard voltage criterion of left ventricular hypertrophy. In the absence of acute infarction, bundle branch block, or digitalisation positive T wave overshoot of the pattern described is a sign of increased ventricular mass.